Pengaruh Model Pembelajaran Berbasis Proyek (Project Based Learning) terhadap Kreativitas Peserta Didik Kelas XI Pada Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti di SMK Negeri 1 Pahae Julu Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Desi Putriany Br. Sihombing; Andar Gunawan Pasaribu; Hasudungan Simatupang; Risden Anakampun; Raikhapoor Raikhapoor (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The purpose of this study is to determine the positive and significant influence of the Project-Based Learning Model on the creativity of grade XI students in the subject of Christian Religious Education and Ethics at SMK Negeri 1 Pahae Julu, North Tapanuli Regency for the 2023/2024 Academic Year. The method used in this study is a quantitative research method with descriptive statistics. The population is all students in class XI of SMK Negeri 1 Pahae Julu which totals 80 people and a sample of 40 people or 50% is determined by the Saturated Sampling technique or in other terms the saturated sample is the census, where all members of the population are sampled. Data was collected with a positive closed questionnaire consisting of four options, namely: a was given a weight of 4, b was given a weight of 3, c was given a weight of 2, d was given a weight of 1 as many as 34 items. Results of data analysis 1) Test of analysis requirements: obtained the value of rxy = 0,315 > rtabel(a=0,05,n=40) = 0,312 thus it is known that there is a positive influence between variable X and variable Y. Test of significant relationship obtained a value of tcal thitung= 2,046 > ttabel(a=0,05,dk=n-2=38)= 2,021 thus there is a significant relationship between variable X and variable Y. 2) Influence test: obtained the regression equation Ŷ=59.337+0.147X. Regression determination coefficient test (r2) = 9.9%. 3) The hypothesis test using the F test obtained Fcal > Ftable, which is 4.18 > 4.09. Thus Ha is accepted and H0 is rejected. It can be seen that the research hypothesis proposed by the author was accepted, namely There is a positive and significant influence between the Project-Based Learning model on the creativity of class XI students in the subject of Christian Religious Education and Ethics at SMK Negeri 1 Pahae Julu, North Tapanuli Regency for the 2023/2024 .